The Influence of Motivation and Family Background on Technopreneur Interest in College Students - Rara Ririn Budi Utaminingtyas; Nur Rini; Taviyastuti Taviyastuti; Irawan Malebra; Nur Imam Nazirhah (Cita konsultindo, 2023)
Business processes today cannot be separated from the role of technology such as production to accelerate it, on the other hand such as media social to improve marketing. Businesses which does not adopt technology in their business will be left behind. The purpose of this research is to know the influence of motivation and family background to technopreneur intention by college student in Tembalang subdistrict, Semarang. This study is quantitative research by approaching data collection through questioner with the number of sample 261 respondent from college student in Polytechnic State of Semarang. By using multiple linear regression analysis tools with regression equation produced Y = 1.783 + 0.412 X1 + 0.313 X2. With T-test result obtained motivation significant Sig =, family background Sig =. It shows partially motivation and family background significantly influence technopreneur intention. The result of F-test obtained by Sig=0.000 which shows simultaneously variable of motivation and family background significantly influence technopreneur intention.